2006
DOI: 10.1101/gad.367606
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian sperm translate nuclear-encoded proteins by mitochondrial-type ribosomes

Abstract: It is widely accepted that spermatozoa are translationally silent. The present study demonstrates, for the first time, incorporation of labeled amino acids into polypeptides during sperm capacitation, which was completely inhibited by mitochondrial translation inhibitors but not by the cytoplasmic translation inhibitor. Unlike 80S cytoplasmic ribosomes, 55S mitochondrial ribosomes were present in polysomal fractions, indicating that these ribosomes are actively involved in protein translation in spermatozoa. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
263
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(277 citation statements)
references
References 37 publications
12
263
0
2
Order By: Relevance
“…In addition, it has been shown that proteins such as those present in the human sperm centrosome are essential for normal syngamy and early embryonic development [38]. Furthermore, it has been recently shown that mammalian sperm translate nuclear-encoded proteins by mitochondrialtype ribosomes [39]. Thus, there are several potential explanations for the proteins identified involved in RNA binding and in transcription in the present work.…”
Section: Resultsmentioning
confidence: 68%
“…In addition, it has been shown that proteins such as those present in the human sperm centrosome are essential for normal syngamy and early embryonic development [38]. Furthermore, it has been recently shown that mammalian sperm translate nuclear-encoded proteins by mitochondrialtype ribosomes [39]. Thus, there are several potential explanations for the proteins identified involved in RNA binding and in transcription in the present work.…”
Section: Resultsmentioning
confidence: 68%
“…35 The incorporation of labelled amino acids into polypeptides during sperm capacitation was completely inhibited by the mitochondrial translation inhibitor D-chloramphenicol but not by the cytoplasmic translation inhibitor cycloheximide, and inhibition of protein translation significantly reduced sperm motility, capacitation and in vitro fertilization rates. 36 Thus, to determine which proteins were translated and to examine the importance of translation during capacitation, we studied the changes in protein expression during capacitation and determined which proteins were newly translated by mitochondrial-type ribosomes using proteomic approaches. A total of 44 proteins were identified with reduced expression in chloramphenicol-treated sperm in comparison with capacitated sperm, and a total of 26 of 44 proteins were involved in some critical processes correlated to sperm-egg interaction events via bioinformatics analysis.…”
Section: Functional Proteomics Of a Mouse Model Of Normal Spermatogenmentioning
confidence: 99%
“…Mitochondrial ribosomedependent translation has been demonstrated to be necessary for Drosophila germ line formation (Amikura et al 2005), and mitochondrial ribosomes are also involved in the translation of nuclear encoded mammalian sperm proteins (Gur & Breitbart 2006). Taking into account the likely function of germ granules in RNA regulation, it will be interesting to find out if the interplay with mitochondria has a role in the germ granulemediated control of gene expression.…”
Section: Pachytene Pirnasmentioning
confidence: 99%